Strategické řízení rozvoje podniku - Vodičková, Sabina (Vysoké učení technické v Brně. Fakulta podnikatelská, 2020)
Diplomová práce se zabývá strategickým řízením rozvoje podniku. Hlavním cílem práce je návrh možného směru strategického rozvoje malého podniku. Cílem teoretické části je vymezit pojmy týkající se dané problematiky, které poslouží v analytické a návrhové části práce. Analytická část má za úkol stanovit potenciál podniku a určit možnosti pro návrhy práce. Poslední část diplomové práce je o formulaci strategických opatření směřujících k rozvoji podniku.

Diploma thesis deals with strategic management of company development. The main purpose is suggestion of a strategic way to develop a small company. The aim of a theoretical part is to define an idea related to certain problematics, which helps in analytical and suggestional part of thesis. Analytical part has to define company potential and options of a work suggestions. The last part of diploma thesis is about formulation strategic measures which leads up to company development.
Strategic Management of Company Development
Keywords: Business strategie; konkurence; SWOT analýza; Business strategy; competition; SWOT analysis